Eksplorasi Denotasi dan Konotasi dalam Kosakata Bahasa Arab: Pendekatan Semantik - Khairani, Putri Dian; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2024)
Denotation and connotation in Arabic vocabulary play an important role in conveying rich and varied meanings, which can be analysed through a semantic approach to understand the nuances of the language more deeply. Although many studies have been conducted on the grammatical and phonological aspects of Arabic, there is a lack of in-depth research on analysing the denotation and connotation of Arabic vocabulary using a semantic approach. This study aims to explore and identify the denotative and connotative meanings of various vocabulary in Arabic and understand how context affects the interpretation of these meanings. The research method used is a literature study by analysing relevant literature, both in the form of books, journal articles, and digital sources, which focus on the theory and application of the semantic approach in Arabic vocabulary analysis. The findings of this study show that the semantic approach can reveal the complexity and diversity of meanings in Arabic vocabulary, as well as provide new insights into how denotation and connotation can contribute to a richer understanding of Arabic texts.